Increasing The Quality of Memorizing The Qur`an for Santri Kalong Through the Sisir Method - Illiyyun Kurniailah; Muhammad Abu Bakar (Universitas Pesantren Kh Abdul Chalim Mojokerto, 2023)
This study aims to describe the implementation of the Sisir method in memorizing the Qur'an and its advantages for students of kalong at PPTQ Baitul Basyar. Researchers used qualitative methods with a case study approach to obtain accountable research results. The results of this study state that the implementation of the sisir method for students of kalong at PPTQ Baitul Basyar has been running systematically and achieving learning objectives with very good results. The quality of Al-Qur'an memorization has met three components: fluent memorization, proportional makharijul huruf, and appropriate tajwid. The thiqah Al-Qur'an hafiz advisor also supports the effectiveness of the Al-Qur'an memorization process in keeping the quality of Al-Qur'an memorization. The advantage of the working method is the sisir method, which memorizes from the end of the juz to the beginning and recites it every five juz. After completing the 30 juz, it is recited from the beginning to the end, which can keep the quality of memorizing the Al-Qur'an students evenly and avoid continuous errors. As for the things that support the achievement of quality and quantity of Al-Qur'an memorization by santri kalong, they include high discipline; having a strong desire to adhere to rote deposit procedures; parental participation in providing exemplary and mentoring; as well as actualizing the verses of the Al-Qur'an that have been memorized through various Islamic boarding schools activities such as being the priest for the Isya prayer, Hifzil Qur'an Competition, and tasmi'.